2002
DOI: 10.1046/j.1462-2920.2002.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

nifH gene diversity in the bacterial community associated with the rhizosphere of Molinia coerulea, an oligonitrophilic perennial grass

Abstract: Rhizosphere associative dinitrogen fixation could be a valuable source of nitrogen in many nitrogen limited natural ecosystems, such as the rhizosphere of Molinia coerulea, a hemicryptophytic perennial grass naturally occurring in contrasted oligonitrophilic soils. The diversity of the dinitrogen-fixing bacteria associated with this environment was assessed by a cloning-sequencing approach on the nifH gene directly amplified from environmental DNA extracts. Seventy-seven randomly picked clones were analysed. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 31 publications
(49 reference statements)
6
54
0
4
Order By: Relevance
“…Moreover, growth of perennial grasses at the same location for several years may lead to the enrichment of the most adapted bacterial populations in both fractions. This was previously observed for dinitrogen-fixing bacteria using a molecular inventory of nifH sequences in a natural meadow [25].…”
Section: Nitrate-dissimilating Pseudomonas Frequency Under Elevated Psupporting
confidence: 74%
See 2 more Smart Citations
“…Moreover, growth of perennial grasses at the same location for several years may lead to the enrichment of the most adapted bacterial populations in both fractions. This was previously observed for dinitrogen-fixing bacteria using a molecular inventory of nifH sequences in a natural meadow [25].…”
Section: Nitrate-dissimilating Pseudomonas Frequency Under Elevated Psupporting
confidence: 74%
“…Lower frequencies of NR Pseudomonas were generally detected in the root fraction (RE) compared to soil (NRS) fraction, for both plants (Fig. 1), with statistically significant differences for some sampling dates ( In the plant-soil systems studied, being for L. perenne cultivated with low N supply [14], or for M. coerulea growing on its native oligotrophic soil [25], the nitrogen availability is clearly limiting. The availability of N is dependant on the N supply (fertilization), N uptake by the plants, and the N transformations, which can imply N losses from the system (i.e., denitrification, leaching).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Hamelin et al (2002) indicated that certain plants mediate favourable niches for nitrogen-fixing bacteria. Plant-specific differences in the nitrogen-fixing bacterial community may be related to plant species, biomass, the chemical composition of litter and root exudates (Shaffer et al, 2000;Bürgmann et al, 2005;Hsu and Buckley, 2009;Knelman et al, 2012).…”
Section: S Tai Et Al: High Diversity Of Nitrogen-fixing Bacteriamentioning
confidence: 99%
“…Surveys of nifH diversity in soil commonly reveal sequence types that correspond to the diverse unidentified diazotrophs (Ueda et al, 1995;Widmer et al, 1999;Piceno and Lovell, 2000;Shaffer et al, 2000;Poly et al, 2001). Evidence indicates that these noncultivated diazotrophs, rather than their cultivated cousins, are the dominant N-fixing organisms in many soil systems (Poly et al, 2001;Hamelin et al, 2002;Tan et al, 2003;Buckley et al, 2007).…”
Section: Introductionmentioning
confidence: 99%